Nutritional Composition and In Vitro Digestibility of Spent Mushroom Substrate Supplemented with Urea and Molasses for Ruminants - Crisostomo, J. C. A.; Manlapig, J. J. D.; Matsui, H.; Ban-Tokuda, T. (Tropical Animal Science Journal, 2025)
This study aims to evaluate the fermentation characteristics and nutritional potential of spent mushroom substrates (SMS), with or without urea and molasses supplementation, in ruminant diets. SMS derived from the cultivation of four mushroom species—Pleurotus ostreatus (Oyster Mushroom, OYS), Flammulina filiformis (Enoki mushroom, ENK), Hypsizygus marmoreus (Bunashimeji mushroom, SMJ), and Lentinula edodes (Shiitake, STK)—were analyzed for proximate composition, in vitro gas and methane (CH₄) production, dry matter digestibility (DMD), and short-chain fatty acid (SCFA). Statistically significant differences were observed among SMS types across all incubation periods (24, 48, and 72 hours) for gas production, CH₄ production, DMD, and SCFA concentrations (p